2017
DOI: 10.1007/s12529-017-9680-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Healthy Lifestyle Education on the Incidence of Metabolic Syndrome in Children during a 13-Year Follow-up

Abstract: This study was funded by National Research Council and Planning and Management Organization and has been reviewed and approved by the Iranian registry of clinical trials (ISRCTN52588395).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The details of more relevant studies that were excluded are demonstrated in supporting information Table S1. Studies were excluded if they: (1) reported correlation coefficient, standard, or unstandard coefficient ( β or B) for MetS prevalence; or reported mean ± SD or mean ± SE or median (interquartile range) of circulating vitamin D levels in those with and without MetS 15,39–41 ; (2) considered MetS as the exposure and serum vitamin D level as the outcome 42,43 ; (3) reported only serum 1,25 (OH)2 D3 levels in both healthy and MetS groups; or assessed the relation of circulating 1,25 (OH)2 D3 and components of MetS 29,44 45 .…”
Section: Methodsmentioning
confidence: 99%
“…The details of more relevant studies that were excluded are demonstrated in supporting information Table S1. Studies were excluded if they: (1) reported correlation coefficient, standard, or unstandard coefficient ( β or B) for MetS prevalence; or reported mean ± SD or mean ± SE or median (interquartile range) of circulating vitamin D levels in those with and without MetS 15,39–41 ; (2) considered MetS as the exposure and serum vitamin D level as the outcome 42,43 ; (3) reported only serum 1,25 (OH)2 D3 levels in both healthy and MetS groups; or assessed the relation of circulating 1,25 (OH)2 D3 and components of MetS 29,44 45 .…”
Section: Methodsmentioning
confidence: 99%
“…The second phase of this study has tested a number of interventions on targeted sub-groups of the population including schoolchildren (97). A recent publication has shown that a healthy lifestyle education can reduce the short term (6 year) risk of the metabolic syndrome in children (98) with similar looking but potentially longer lasting benefits in adolescents (99).…”
Section: Preventing the Metabolic Syndromementioning
confidence: 99%
“…It could be that these are safe in normal-weight individuals without any heredity for MS but possibly not in women with an increased metabolic risk, in whom insulin sensitivity may already be disturbed [47]. The role of healthy diet, physical activity, and sleep are already well-known health promoting factors [48]; however, these factors in the present study displayed only a marginal impact, possibly due to the subjective nature of the data.…”
Section: Discussionmentioning
confidence: 72%